2008
DOI: 10.1186/1749-8090-3-26
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac retransplantation is an efficacious therapy for primary cardiac allograft failure

Abstract: Background: Although orthotopic heart transplantation has been an effective treatment for endstage heart failure, the incidence of allograft failure has increased, necessitating treatment options. Cardiac retransplantation remains the only viable long-term solution for end-stage cardiac allograft failure. Given the limited number of available donor hearts, the long term results of this treatment option need to be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
1
16
0
4
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13] Most reports suggest caution about retransplantation because its outcomes are inferior to those of primary transplantation, and conclude that retransplantation should thus be considered only for select patients. On the other hand, Atluri and colleagues 12 found that meticulous perioperative care improved the results of retransplantation and concluded that it was an efficacious procedure with potentially wider application. A recent report on 23 patients who had retransplantations over a RESEARCH 25-year period at an experienced heart transplant centre suggested improved late survival results when repeat transplantation was performed for graft vascular disease or chronic graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] Most reports suggest caution about retransplantation because its outcomes are inferior to those of primary transplantation, and conclude that retransplantation should thus be considered only for select patients. On the other hand, Atluri and colleagues 12 found that meticulous perioperative care improved the results of retransplantation and concluded that it was an efficacious procedure with potentially wider application. A recent report on 23 patients who had retransplantations over a RESEARCH 25-year period at an experienced heart transplant centre suggested improved late survival results when repeat transplantation was performed for graft vascular disease or chronic graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that outcomes of cardiac re-transplantation are worse compared with those of the first transplant (1-3), while cardiac re-transplantation is thought to be a sole definitive treatment strategy for cardiac allograft failure (4).…”
Section: Introductionmentioning
confidence: 99%
“…Популяция реципиентов с трансплантирован-ным сердцем непрерывно увеличивается [2], что ведет к возрастанию числа пациентов с недоста-точностью сердечного трансплантата (НСТ). НСТ чаще всего обусловлена одной из трех причин: острое отторжение, первичная НСТ, васкулопатия трансплантированного сердца (ВТС).…”
unclassified
“…Несомненно, возможность и клинический успех выполнения РеТС определяются клиническим опы-том и объемом выполняемых операций в конкрет-ном клиническом центре. В течение двух последних десятилетий был накоплен значительный опыт в пред-, интра-и постоперационном ведении паци-ентов с трансплантированным сердцем [2], пред-ложены критерии подбора донора и реципиента, изучены различные интра-и периоперационные технологические аспекты, достигнут значительный успех в иммуносупрессивной терапии.…”
unclassified
See 1 more Smart Citation